Utilization Of Natural Resources as a Livelihood as Well As a Tourist Destination for the Community of Desa Les, Tejakula - Diputra, I Putu Nova; Budiarta, I Wayan; Putra, I Kadek Agus Juniartana; Rahayu, Ni Made Istri Wahyuni; Sastradewi, Ni Luh Putu Diah; Pratama, Putu Redy Kusuma; Putra, Komang Wahyu Adi; Sugiantari, I Gusti Ayu Ngurah (Universitas Pendidikan Ganesha, 2025)
Les Tourism Village is a village located in Tejakula District, Buleleng Regency which has beautiful Natural Resources. The utilization of Natural Resources in Les Tourism Village is very much felt, starting from being used as a tourist spot to becoming a source of livelihood until now. In 2024, Les Tourism Village was successfully named the Best Tourism Village by the Ministry. In the Observations that have been carried out, Les Tourism Village has various kinds of tourism and livelihood places. Starting from tourism places, Les Tourism Village has various great places to visit such as Yeh Mampeh Waterfall which is one of the beautiful views in Les tourism village, not only that, Les tourism village also provides beautiful hills and underwater views. The tourism village provides hill trekking and snorkeling or diving. Furthermore, the Natural Resources that are utilized as a source of livelihood, the sources of livelihood in Les Tourism Village vary from racing, farming, fishermen and traders. The most popular livelihood today is salt farmers. These salt farmers have begun to be recognized and have begun to form organizations by Bumdes. Through the tourist destinations and livelihoods in Les Tourism Village, it can add to and develop the development of Les Village, especially in the Economic Sector.